The impact of digital village policy implementation on the innovation and establishment of new agricultural operators: evidence from China - Gao, Meng; Mao, Xiaoqian; Wang, Zijun; Feng, Yangyang (Frontiers in Sustainable Food Systems, 2025)
Cultivating new agricultural operators is crucial for revitalizing rural industries and promoting rural development. However, existing literature has not fully explored the impact of digital village policies on the innovation and establishment of new agricultural operators (IENAO). To fill this research gap, this study aims to empirically analyze the impact of digital village policies, represented by China’s National Digital Village Pilot Policy (CNDVPP), on IENAO. To achieve this objective, the study employs a Difference-in-Differences (DID) model, utilizing county-level panel data from 2014 to 2022. The results show that: (1) the CNDVPP has a significant positive effect on IENAO. After the policy implementation, IENAO level increased by 0.841 standardized units, which corresponds to an increase from the median to the 58th percentile; (2) key mechanisms driving this impact include the return of agricultural labor (ALR) and the transfer of land factors (LTF): specifically, the CNDVPP significantly promotes ALR, with the estimated effect being 0.059, and facilitates LTF by 0.545; (3) the policy’s effect is more substantial in regions with lower education levels, weaker clan networks, and less favorable market conditions. Regional tailoring of policy is needed for boosting digital training in areas with lower education, weaker clan networks, and less favorable market conditions. We recommend community-based cooperation platforms for easier information sharing. These measures would help enhance IENAO, thereby driving rural revitalization and fostering sustainable development.